(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Textile industry sex in the fibrous materials titish, savash, comb, pahmoqlash in the process dust, painting, paints prepare, ohorlash, tuklarni will to exert in the process of chemicals, harmful gases are separated out. Textile industry, especially, his starting the process of most of many common harmful ingredients – powder. It all work is the production of sex and the enterprise in the territory of the atmosphere in a long time, landing, flying, walking can.